LITERASI KEUANGAN: Tips Menabung untuk Siswa Sekolah Dasar di SDIT Al Islami Tajur Halang Bogor - Septiowati, Rini; Purwatiningsih, Purwatiningsih; Sari, Silvia (Jurnal PKM Manajemen Bisnis, 2025)
Financial literacy is an important activity in accounting. Introducing financial literacy to children can be done by introducing children to the values ​​of money and the culture of saving. The importance of saving for school students is not only to get their own money, but to be accustomed to strong self-management so that they can become wise people who manage their finances, do not live excessively or wastefully, can think anticipatory to unexpected situations and are able to manage finances in the future. will come. The goal of saving is to get used to living frugally. Living frugally means not being wasteful. Expenditures are adjusted to needs and meet large needs in the future. The aim of the service is to train students to record simple financial reports in managing money. The service team uses a training method through stage four. Lectures, tutorials, discussions and evaluations. This service was carried out at SDIT AL Islami Tajur Halang Bogor on October 10 2024, which was attended by 25 students. The result of this training is that students participate in the training enthusiastically. Delivery of light material, according to needs, and easy to understand, direct training assistance, exciting discussions, sufficient training duration, and evaluation as a benchmark for success. This is an effort to manage student finances and minimize waste.